Aerobic digestion reduces the quantity of antibiotic resistance genes in residual municipal wastewater solids - Burch, Tucker R.; Sadowsky, Michael J.; LaPara, Timothy M. (Frontiers in Microbiology, 2013)
Numerous initiatives have been undertaken to circumvent the problem of antibiotic resistance, including the development of new antibiotics, the use of narrow spectrum antibiotics, and the reduction of inappropriate antibiotic use. We propose an alternative but complimentary approach to reduce antibiotic resistant bacteria by implementing more stringent technologies for treating municipal wastewater, which is known to contain large quantities of antibiotic resistant bacteria and antibiotic resistance genes (ARGs). In this study, we investigated the ability of conventional aerobic digestion to reduce the quantity of ARGs in untreated wastewater solids. A bench-scale aerobic digester was fed untreated wastewater solids collected from a full-scale municipal wastewater treatment facility. The reactor was operated under semi-continuous flow conditions for more than 200 days at a residence time of approximately 40 days. During this time, the quantities of tet(A), tet(W), and erm(B) decreased by more than 90%. In contrast, intI1 did not decrease, and tet(X) increased in quantity by 5-fold. Following operation in semi-continuous flow mode, the aerobic digester was converted to batch mode to determine the first-order decay coefficients, with half-lives ranging from as short as 2.8 days for tet(W) to as long as 6.3 days for intI1. These results demonstrated that aerobic digestion can be used to reduce the quantity of antibiotic resistance genes in untreated wastewater solids, but that rates can vary substantially depending on the reactor design (i.e., batch versus continuous-flow) and the specific ARG.